Involvement and Participation of Students With Severe Disabilities in SWPBIS. (November 2018) - Kurth, Jennifer A.; Zagona, Alison L.
With more schools implementing Schoolwide Positive Behavioral Interventions and Supports (SWPBIS) and achieving valued student outcomes associated with these efforts, the inclusion of students with extensive and pervasive support needs (i.e., "severe" disabilities) in this tiered system must be considered. These students remain programmatically and physically separated from general education instruction and activities. Given that SWPBIS is implemented in general education settings and it is designed to support all students, the purpose of this study was to investigate SWPBIS coaches' perceptions of the involvement of students with extensive support needs in SWPBIS processes and procedures within one state. Findings suggest the coaches believe that students with extensive support needs are physically and programmatically separated from Tier 1 SWPBIS instruction and activities, with few general educators expressing participation in facilitating their involvement. Implications and recommendations for these findings are provided.